1999
DOI: 10.1016/s1058-3300(99)00002-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of psychological barriers in the conditional moments of major world stock indices

Abstract: This study investigates the existence of psychological barriers in the Dow Jones Industrial Average, the S&P 500, and six foreign stock indices. It is believed by many in the investment community that index levels that are multiples of 100 serve as barriers, and that markets may resist crossing these barriers. Although return dynamics in the neighborhood of barrier points are not identical for all series studied, we find aberrations in the conditional means and variances consistent with psychological barriers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
47
7
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(72 citation statements)
references
References 20 publications
17
47
7
1
Order By: Relevance
“…It is also noteworthy that the variance tends to be higher in most stocks in post-crossing periods than in pre-crossing periods, which is consistent with the possibility of increased technical trading in the post-crossing period (Cyree et al, 1999).…”
Section: Conditional Effects Testsupporting
confidence: 71%
See 4 more Smart Citations
“…It is also noteworthy that the variance tends to be higher in most stocks in post-crossing periods than in pre-crossing periods, which is consistent with the possibility of increased technical trading in the post-crossing period (Cyree et al, 1999).…”
Section: Conditional Effects Testsupporting
confidence: 71%
“…They did not find any indication of the existence of psychological barriers in those three indices. Cyree, Domian, Louton and Yobaccio (1999) showed that the last two digits of the DJIA, the S&P 500, the Financial Times U.K. Actuaries (London) and the DAX are not equally distributed. Prices next to barriers turn up less frequently than prices in a more distant position.…”
Section: Previous Findingsmentioning
confidence: 99%
See 3 more Smart Citations